VI‐RADS for Bladder Cancer: Current Applications and Future Developments. Issue 1 (17th September 2020) - Panebianco, Valeria; Pecoraro, Martina; Del Giudice, Francesco; Takeuchi, Mitsuru; Muglia, Valdair F.; Messina, Emanuele; Cipollari, Stefano; Giannarini, Gianluca; Catalano, Carlo; Narumi, Yoshifumi
Abstract : Bladder cancer (BCa) is among the ten most frequent cancers globally. It is the tumor with the highest lifetime treatment‐associated costs, and among the tumors with the heaviest impacts on postoperative quality of life. The purpose of this article is to review the current applications and future perspectives of the Vesical Imaging Reporting and Data System (VI‐RADS). VI‐RADS is a newly developed scoring system aimed at standardization of MRI acquisition, interpretation, and reporting for BCa. An insight will be given on the BCa natural history, current MRI applications for local BCa staging with assessment of muscle invasiveness, and clinical implications of the score for disease management. Future applications include risk stratification of nonmuscle invasive BCa, surveillance, and prediction and monitoring of therapy response. Level of Evidence: 3 Technical Efficacy Stage: 2